PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS WEB PADA MATERI PERKEMBANGBIAKAN TUMBUHAN DAN HEWAN UNTUK SISWA SMP KELAS IX DENGAN METODE TUTORIAL - Marlina Marlina; Andi Ichsan Mahardika; Nuruddin Wiranda (Pendidikan Komputer FKIP Universitas Lambung Mangkurat, 2023)
The tutorial method is an interesting technology learning model, where students must actively participate in the learning process and the computer becomes a teacher. This method is able to encourage students to actively participate in learning and provide a thorough understanding. Therefore, the aims of this study were (1) to develop web-based interactive learning media on plant and animal breeding material for class IX junior high school students by (2) to find out the feasibility of web-based interactive learning media on plant and animal breeding material for class IX junior high school students with the tutorial method. This study used the Research and Development (R&D) method with the ADDIE development model, involved 25 students and 1 teacher at SMPN 13 as research trial subjects. Data was collected through validity assessment, questionnaires and tests. The instruments used included material expert validation sheets, media expert validation sheets, teacher and student response questionnaires, lesson plans implementation sheets, and learning achievement tests. The results of the study show that (1) web-based interactive learning media is stated to be very valid based on the results of assessments from material experts and media experts. (2) web-based interactive learning media is stated based on the results of the teacher and student response questionnaires, as well as lesson plans implementation sheets. In addition, (3) web-based interactive learning media is declared effective based on student learning outcomes tests. Thus, web-based interactive learning media regarding plant and animal breeding material for junior high school students in grade IX using the tutorial method is declared feasible and can be used in learning because it meets the criteria of validity, practicality and effectiveness.